Annular rectal constriction caused by infiltrating bladder carcinoma a case report - Katayama, Hiromichi (Hinyokika kiyo. Acta urologica Japonica, 2010)
A 64-year-old man was referred to our hospital with chief complaints of gross hematuria and pollakisuria. Cystoscopic examination showed non-papillary broad basis tumor on the left lateral wall involving the left ureteral orifice. Computed tomography (CT) and magnetic resonance imaging revealed left hydronephrosis and urinary bladder tumor which extended outside of the bladder wall. Transurethral biopsy showed grade 3 urothelial carcinoma with glandular differentiation including signet ring cells. Radical cystectomy, left nephrureterectomy and right ureterocutaneostomy were performed. Pathological examination showed urothelial carcinoma; pT3aN0. Lymph node metastasis occurred five months later. Three courses of M-VAC chemotherapy (methotrexate, vinblastine, adriamycin, cisplatin) were done with little effectiveness. Sixteen months after the operation, he complained of anorexia and tenesmus, and CT showed annular thickening of the rectal wall. A fecal diversion was performed, but he died two months later